Reimagining the Heimat in Elfriede Jelinek's Women as Lovers, Lust, and Greed - Maranan, Danelle Rose A. (College of Arts and Letters, University of the Philippines Diliman, 2017)
For over 200 years, the idea of Heimat (homeland) has been idealized and immortalized in German-language literature. It is a key concept in understanding the construction of national and cultural identity of German-speaking people. This study attempts to examine, through the lens of spatial theory and Heimat discourse, how Elfriede Jelinek challenges the traditional notion of Heimat embodied in the space of the Austrian countryside in her novels - Women as Lovers, Lust, and Greed. In analyzing the literary representation of rural space in Jelinek's novels, this study shows that Heimat is a space needs to be re-examined and deconstructed. The analysis shows that, through the construction of an anti-Heimat, Jelinek has exposed the myths of Heimat and the Austrian cultural identity constructed based on historical amnesia and a false sense of victimhood.